Leading through crisis: Understanding instructional leadership and educational resilience in India - Dhandapani, Sudha; Kaur, Kamaljeet (Journal of Interdisciplinary Studies in Education, 2026)
This qualitative case study examines how instructional leadership practices enacted by school principals contribute to educational resilience during crises, including the COVID-19 pandemic and recurrent natural disasters (earthquakes and landslides) in Uttarakhand, India. Drawing on semi-structured interviews with 50 school principals and complementary field observations, the study investigates leadership strategies that supported teachers’ professional development, sustained instructional continuity, strengthened communication, and fostered community engagement. Findings indicate that principals who prioritized instructional guidance, collaborative decision-making, and adaptive planning were more successful in maintaining student learning outcomes and minimizing dropout risks during periods of disruption. The study reveals a strong association between sustained instructional leadership and the development of resilient school systems capable of responding effectively to crisis conditions.